Treatment of renal hydatid echinococcosis - Lockart, Jorge (Cirugía del Uruguay, 2020)
The surgical treatment of renal echinococcosis is discussed in the light of wide local experience. A detailed survey is carried out of possible methods from conservative procedures to radical ones, that is, from mere marsupialization or direct or indirect cystectomy to partial nephrectorpy or total cystectomy. Attention is drawn to the advantages of renal gammagram for surgical indications, as well as the likelihood of conservative treatment in conjunction with transcystic pyeloureteral drainage.